INFLUENCE OF THE EVENTS OF FEBRUARY 1917 ON IDEAS OF LOCAL COMMUNITIES ABOUT THE STATE SYSTEM OF CAUCASUS PEOPLES - Ambartsumyan, Karine Razmikovna (Közép-Európai Közlemények, 2020)
The article studies the development of ideas of Caucasus communities as regards their status and position in Russia in 1917. With the reference to memoirs of contemporaries and participants of the events it is claimed that the overthrow of Russian monarchy became, on the one hand, impetus for activity in the regions as political and intellectual elite sought to prepare and form a part of Russian federative state as autonomy. On the other hand, as the Interim government grew weak centrifugal forces intensified. The unity of Transcaucasia and the North Caucasus in their political and social development during February-October 1917 is revealed.